CHALLENGES FOR INDONESIAN EFL STUDENTS IN ENGLISH ACADEMIC WRITING - Pasaribu, Arsen Nahum; Pasaribu, Tiara Kristina; Siahaan, Restu Berkah; Sitompul, Dewi Sartika (English Review: Journal of English Education, 2024)
This research aims to examine the challenges faced by Indonesian EFL students in academic writing, specifically the errors they made while writing scholarship application essays. The study focused on identifying syntactical and morphological errors and understanding their sources and reasons. The data consisted of 20 essays from third-semester students in an academic writing course at a private Indonesian university. Two English language lecturers reviewed the essays twice to identify the errors. The findings revealed that syntactic errors were the most common, with 132 instances (61.69%), followed by punctuation and capitalization errors with 50 instances (23.37%), and morphological errors were the least frequent with 32 instances (14.94%). Interlingual, or native language interference, was found to be the primary source of these errors. The main factor of making errors is the lack of previous experience and knowledge about the conventions of academic writing and the expectations of the institution they are studying at. This study offers teaching recommendations for EFL teachers, emphasizing the importance of considering the impact of learners' native language besides providing appropriate grammar instruction as the key to effective teaching for ESL teachers.